STRUCTURE OF IDEALISTIC FUZZY SOFT Γ-NEAR-RING - Ersoy, Bayram Ali; Onar, Serkan; Davvaz, Bijan; Hila, Kostaq (UNIV POLITEHNICA BUCHAREST, SCI BULL, 2015)
The concept of idealistic fuzzy soft Gamma-near-ring is introduced and some properties of idealistic fuzzy soft Gamma-near-ring are given. Also, the definitions of homomorphic and inverse image of idealistic fuzzy soft Gamma-near-ring are introduced and some theory of them is considered.
Keywords: Gamma-near-ring; idealistic fuzzy soft Gamma-near-ring; SETS; Mathematics; Physics